Magnetic annihilation of the dark mode in a strongly coupled bright-dark terahertz metamaterial - Manjappa, Manukumara (2020)
Dark mode in metamaterials has become a vital component in determining the merit of the Fano type of interference in the system. Its strength dictates the enhancement and suppression in the amplitude and Q-factors of resulting resonance features. In this work, we experimentally probe the effect of strong near-field coupling on the strength of the dark mode in a concentrically aligned bright resonator and a dark split ring resonator (SRR) system exhibiting the classical analog of the electromagnetically induced transparency effect. An enhanced strong magnetic field between the bright-dark resonators destructively interferes with the inherent magnetic field of the dark mode to completely annihilate its effect in the coupled system. Moreover, the observed annihilation effect in the dark mode has a direct consequence on the disappearance of the SRR effect in the proposed system, wherein under the strong magnetic interactions, the LC resonance feature of the split ring resonator becomes invisible to the incident terahertz wave.